Simulación de Nanosensores para Detectar Partículas Contaminantes Utilizando Sistemas de Información - Cano Olivera, Luís Eduardo; Pérez Castillo, José Nelson (Ingeniería, 2007)
The nanoscience has waked up the interest of the scientific communities, companies and students at world-wide level that within that frame, and it given the few advances that have been made in the country, it’s looked for in to experiment and deepen in this topic. Between the most promising applications of this scientific and technological revolution they are: the energy, agriculture, the treatment of waters, the treatment of diseases, the drug administration, the food processing, the contamination, the construction, the detection and the control of plagues.[3] Given the frame of action that has the Nanotechnology, and by its magnitude and complexity, one has looked for within this approach, centralizing in the Nanosensonic and to see its applicability in the Information Systems as opposed to the Conventional Microsensonic to treat within the many existing applications, the problem of the environmental contamination, considered by many like badly that affects to the society in general with different diseases and symptoms generated by the outsourcing that cause them.[21]